Conditions for transplantation of primordial germ cells in the yellowtail tetra, Astyanax altiparanae - Coelho, Geovanna Carla Zacheo [UNESP]; Carvalho, Gabriella Braga; Monzani, Paulo Sergio [UNESP]; Lopez, Lucia Suarez [UNESP]; Do Nascimento, Nivaldo Ferreira; Senhorini, José Augusto [UNESP]; Yasui, George Shigueki [UNESP] (UPV/EHU Press, 2023)
Biotechniques, including surrogate propagation derived from primordial germ cell (PGC) transplantation, are valuable tools for the reconstitution of endangered fish species. Although promising, there are no previous studies reporting such approaches using neotropical fish species. The aim of this study was to establish germline chimeras in neotropical fish by using the yellowtail tetra Astyanax altiparanae as a model species of the order Characiformes. Germline chimeras were obtained after transplantation of PGCs cultivated under different conditions: saline medium and supplemented with DMEM, amino acids, vitamins, glutamine, pyruvate, and fetal bovine serum, and subsequently transplanted into A. altiparanae triploids and triploid hybrids from the cross between A. altiparanae () and A. fasciatus (). The results indicate ectopic migration in host embryos after transplantation of PGCs cultivated in saline medium. However, PGCs cultivated in supplemented medium migrated to the region of the gonadal ridge in 4.5% of triploid and 19.3% in triploid hybrid. In addition, the higher expression of dnd1, ddx4 and dazl genes was found in PGCs cultivated in supplemented culture medium. This indicates that the culture medium influences the maintenance and development of the cultivated cells. The expression levels of nanos and cxcr4b (related to the differentiation and migration of PGCs) were decreased in PGCs from the supplemented culture medium, supporting the results of ectopic migration. This is the first study to report the transplantation of PGCs to obtain germline chimera in neotropical species. The establishment of micromanipulation procedures in a model neotropical species will open new insights for the conservation of endangered species.
Keywords: biotechnology; genebank; germline chimera; primordial germ cells; teleost; transplant